THE SOCIALIZATION OF PHBS ABOUT HOUSEHOLD SANITATION IN TULUNG KAKAN, BUMIRATU NUBAN, LAMPUNG TENGAH - Annissa Valentina (INTASTAWIT Journal (Indonesian Tasamuh, Tawassuth, I'tidal, dan Tawazun), 2020)
Purpose of this community dedication is present the significancy of household sanitary hygiene in public settlement environment. Sanitary hygiene as one of public health aspect to create health public environment. This activity in the formed of socialization formerly did generally in public hall, lalu dilnjutkan with socialization personally door to door of people who do not yet good sanitation facilities. Formerly data was get from officials who had been did survey to people in this village who have not been sanitation facilities like toilet for defecation until food residual and other rubbish from household waste. This activity community dedication is expected to give education to community for more police sanitation in people household.